Picking the crucial language technologies and how Wikipedia can help: the Welsh experience - Morlais, Gareth (Septentrio Conference Series, 2021)
When you're making plans to get people using your language as much and as often as possible, there's a list of things related to Wikipedia which can really help. I'll share our experience with the Welsh language. Supporting the Welsh-language Wikipedia community forms Work Package 15 of 27 in the Welsh Government's Welsh Language Technology Action Plan https://gov.wales/sites/default/files/publications/2018-12/welsh-language-technology-and-digital-media-action-plan.pdf. We like supporting Welsh language Wikipedia editing workshops, video workshops and other channels that encourage people to create and publish Welsh-language video, audio, graphic and text content because we're on a mission to try to help double daily use of Welsh by 2050. I'll share developments we're funding in speech, translation and conversational AI. The partners we're giving grants to publish what they develop under open licence. So we can share what we've funded with many companies. We think Microsoft might have used some to make their new synthetic voices in Welsh. We're excited by the potential Wikidata offers. We'll look at its potential in populating Welsh maps this year. We've already used Wikipedia search data as a way of prioritising the training of a Welsh virtual assistant. Welsh may not be spending as much as Icelandic and Estonian do on language technologies, but we'd like to share what we're learning as a smaller language about the important areas to focus on and how Wikipedia can help.